2016
DOI: 10.1016/j.ydbio.2016.05.012
|View full text |Cite
|
Sign up to set email alerts
|

An unregulated regulator: Vasa expression in the development of somatic cells and in tumorigenesis

Abstract: Summary Growing evidence in diverse organisms shows that genes originally thought to function uniquely in the germ line may also function in somatic cells, and in some cases even contribute to tumorigenesis. Here we review the somatic functions of Vasa, one of the most conserved “germ line” factors among metazoans. Vasa expression in somatic cells is tightly regulated and often transient during normal development, and appears to play essential roles in regulation of embryonic cells and regenerative tissues. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 105 publications
3
23
0
Order By: Relevance
“…On observation of the cells, we found that the DDX4 knockout cells typically formed incomplete spindles (Fig. e) and no longer proliferated significantly, which is also a consistent phenotype reported in germline stem cells and in some embryonic cells . In this study, however, we emphasize a population‐based study.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…On observation of the cells, we found that the DDX4 knockout cells typically formed incomplete spindles (Fig. e) and no longer proliferated significantly, which is also a consistent phenotype reported in germline stem cells and in some embryonic cells . In this study, however, we emphasize a population‐based study.…”
Section: Resultssupporting
confidence: 83%
“…Furthermore, as DDX4 is generally not expressed in benign adult somatic cells, it could serve as a potential target to detect early steps of malignancy among heterogeneous tumors and/or for a cancer therapy in the future. Our results suggest that another germline factor, PIWI, also appears to be expressed with DDX4 in these same cancer cells, and thus may serve as important co‐target for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both transcripts and protein of one of the key germline determinants in the PGCs, vasa, localise to this domain, as do nanos and piwil1 and piwil2 (Wu et al, 2011;Zhang et al, 2013;Dailey et al, 2016). Vasa plays a general role in regulating translation in the soma (Poon et al, 2016) and nanos2 has recently been shown to transiently repress translation in PGCs via inhibition of eIF1a in sea urchins (Ouhlen et al, 2017). Thus, we might expect expression of such genes in the adult regenerating tail.…”
Section: Somatic Progenitorsmentioning
confidence: 99%
“…So far the mRNA VASA expression in normal somatic tissues has only been detected during embryogenesis. [ 1 ] The vas gene was originally identified in Drosophila (vasa), later in the mouse (Mouse vasa homolog, MVH) and in humans (VASA). [ 2 7 ] It maps on chromosome 5q and encodes a DEAD-box protein with ATP-dependent RNA-helicase activity.…”
Section: Introductionmentioning
confidence: 99%